If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8n + -6 = 9n Reorder the terms: -6 + 8n = 9n Solving -6 + 8n = 9n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-9n' to each side of the equation. -6 + 8n + -9n = 9n + -9n Combine like terms: 8n + -9n = -1n -6 + -1n = 9n + -9n Combine like terms: 9n + -9n = 0 -6 + -1n = 0 Add '6' to each side of the equation. -6 + 6 + -1n = 0 + 6 Combine like terms: -6 + 6 = 0 0 + -1n = 0 + 6 -1n = 0 + 6 Combine like terms: 0 + 6 = 6 -1n = 6 Divide each side by '-1'. n = -6 Simplifying n = -6
| 0.2-0.01(x+2)=-0.03(2-x) | | 2(x-5)=4x-2(x-5) | | -7x+8=-20 | | 4(x-2)+6=6x-2(2+x) | | -1.66x+.66=-11 | | 18m+30=66 | | 2(2+4)= | | 0.4(x+20)-0.8X=44 | | 5(92-5x)=27 | | 0.25n+0.1=9.8 | | 7-4w=-10 | | 6x-15x+-5=58 | | 4d=27 | | X^2+2=3 | | -3(3s-5)-15=-3(7s+1)-5 | | 8y+3(y-7)=3(y+2)-4 | | -x^2-10x=25 | | 0.5x-4.8=-2.3 | | 2/3(x-8)=x+2 | | 3g-12=9 | | -3(t-3)+9t=4t-1 | | -9(t-8)-(t+8)=3 | | 7(6x+4)+2=42x+30 | | -4y+6=-2(4y+5) | | r=4k+4w | | X^2+10=2 | | 9x-3=9(x-2) | | 3(x-5)=2(x+2) | | 7+9(x-8)=10-3(x-5) | | X^2+2x-324=2x | | 3/4(x-7)=x+2 | | 11x^2+x-2=0 |